PENERAPAN PROTOKOL PENCEGAHAN PENYEBARAN CORONA VIRUS DISEASE 2019 (COVID-19) PADA PENYELENGGARAAN PROYEK KONSTRUKSI - Hikmah Maya Sari (MECHA JURNAL TEKNIK MESIN, 2021)
The Covid-19 pandemic has weakened various sectors in Indonesia, including the construction sector. Restrictions on social interactions and associations of people in public places stop construction work and are temporarily delayed. In connection with the development of the COVID-19 pandemic in Indonesia, the Ministry of PUPR issued PUPR Minister Instruction No. 02/2020 concerning the Protocol to Prevent the Spread of COVID-19 in the implementation of Construction Services which was signed on March 27 2020. In general, the PUPR Ministerial Instruction contains a mechanism regarding the COVID-19 prevention protocol in the implementation of construction services, namely the COVID-19 prevention protocol scheme in the implementation of construction services and its mechanisms. The purpose of this study was to find out whether the X Project in Samarinda had implemented the COVID-19 prevention protocol in accordance with the Instruction of the Minister of PUPR. The protocol for prevention and handling of COVID-19 in the implementation of the X Project has largely followed the PUPR Minister's Instruction. The implementation of the protocol for preventing the spread of COVID-19 that needs to be added is (1) Construction Work Service Providers are required to provide additional vaccines, vitamins and nutrients to increase worker immunity; (2) If a worker in the field is COVID-19 Patient Under Surveillance (PDP), work must be temporarily suspended by the Service User and / or Service Provider for at least 14 (fourteen) working days. Keywords: Corona Virus Disease 2019 (COVID-19), construction services, protocols for prevention and spread of COVID-19